Islamic Microfinance: Addressing Poverty Alleviation and Entrepreneurship Development - Hotman, Hotman; Hilman, Haim; Ahmad, Norzieiriani (Accounting Studies and Tax Journal (COUNT), 2024)
This research investigates the role of Islamic microfinance in poverty alleviation and entrepreneurship development. Using a systematic literature review approach, this research analyzes the relationship between types of financing, access to Islamic financial services, government policies, and the level of entrepreneurship with household income and the development of micro and small businesses. The findings show that Islamic microfinance can be an effective instrument in strengthening the economic base of underprivileged communities, especially through the integration of Islamic principles in the financial system.